Analysis of medical students’ knowledge about early detection of colon and rectum cancer (Research, Society and Development, 2023)
Colorectal cancer (CRC) is the second most prevalent cancer in both sexes in Brazil, second only to prostate cancer in men and breast cancer in women. Mortality from this type of cancer is still very high, reaching 50% of cases according to INCA data. In addition, when diagnosed early, CRC has an excellent prognosis, since this cancer is symptomatic only in more advanced stages and people often seek the doctor only when they have signs and symptoms of the disease, which ends up making it difficult to diagnose in the early stages, which shows us a lack of effectiveness of screening programs for CRC in Brazil. In view of this, the study aims to analyze the knowledge of medical students at UniCesumar university, from Maringá, regarding the early detection of CRC. For this, a questionnaire was prepared with 21 questions on the subject, by google forms. The sample population consisted of 271 students enrolled in the medical course from the 1st to the 8th period, with the aim of comparing the evolution of students' knowledge between periods. After applying the questionnaire and analyzing the results, it was observed that there really was a significant evolution of knowledge between the periods, however, there is still a deficit of knowledge about the subject by all students, which shows us a need for improvement about this subject by the universities, so that medical students can adequately guide patients in their medical practice.